Effect of microsurgical technique for root coverage using modified coronally advanced flap with connective tissue graft- Randomized controlled clinical trial - N. K. Savithri; Sangeetha Subramanian; P. S. G. Prakash; Devapriya Appukuttan (Wolters Kluwer Medknow Publications, 2022)
Background: The aim of the study was to compare the root coverage percentage and other clinical outcomes in Millers Class I and Class II gingival recessions (GR) treated with modified coronally advanced flap (MCAF) combined with connective tissue graft (CTG) using macro and microsurgical approaches. Materials and Methods: In this controlled clinical trial, a total of 32 Miller's Class I and Class II GR defects were randomly assigned to the control and test groups (16 in each group). All the patients were treated with MCAF with CTG as the root coverage procedure. For the control and test groups, the procedure was performed using a macro and microsurgical approach, respectively. Clinical parameters were assessed at baseline and in 6th month. Wilcoxon signed-rank test was used to compare the values between baseline and 6 months. Statistical significance was set at P < 0.05. 1 week after surgery, wound healing index (WHI) and Visual Analog Scale (VAS) scores were recorded. Results: Intragroup comparisons revealed significant improvement in all the parameters in both the groups at 6 months. The proportion of root coverage achieved in the control and test groups was 78% and 86%, respectively. At 6 months, the root coverage percentage between the study groups showed no significant difference (P = 0.207). Intergroup analysis of WHI and VAS scores showed better healing and less postoperative pain in the microsurgical group compared to macrosurgical group (P < 0.05). Conclusion: At 6 months, there were no significant differences in root coverage percentage or other clinical parameters between the groups based on whether a macro or microsurgical method was used. However, better wound healing, less pain, and discomfort were observed in the microsurgical group.